Epigenetic Modifications Associated to Neuroinflammation and Neuropathic Pain After Neural Trauma - Penas, Clara; Navarro, Xavier (Frontiers in Cellular Neuroscience, 2018)
Accumulating evidence suggests that epigenetic alterations lie behind the induction and maintenance of neuropathic pain. Neuropathic pain is usually a chronic condition caused by a lesion, or pathological change, within the nervous system. Neuropathic pain appears frequently after nerve and spinal cord injuries or diseases, producing a debilitation of the patient and a decrease of the quality of life. At the cellular level, neuropathic pain is the result of neuronal plasticity shaped by an increase in the sensitivity and excitability of sensory neurons of the central and peripheral nervous system. One of the mechanisms thought to contribute to hyperexcitability and therefore to the ontogeny of neuropathic pain is the altered expression, trafficking, and functioning of receptors and ion channels expressed by primary sensory neurons. Besides, neuronal and glial cells, such as microglia and astrocytes, together with blood borne macrophages, play a critical role in the induction and maintenance of neuropathic pain by releasing powerful neuromodulators such as pro-inflammatory cytokines and chemokines, which enhance neuronal excitability. Altered gene expression of neuronal receptors, ion channels, and pro-inflammatory cytokines and chemokines, have been associated to epigenetic adaptations of the injured tissue. Within this review, we discuss the involvement of these epigenetic changes, including histone modifications, DNA methylation, non-coding RNAs, and alteration of chromatin modifiers, that have been shown to trigger modification of nociception after neural lesions. In particular, the function on these processes of EZH2, JMJD3, MeCP2, several histone deacetylases (HDACs) and histone acetyl transferases (HATs), G9a, DNMT, REST and diverse non-coding RNAs, are described. Despite the effort on developing new therapies, current treatments have only produced limited relief of this pain in a portion of patients. Thus, the present review pretends to contribute to find novel targets for chronic neuropathic pain treatment.